PERANAN MANAJEMEN PERUBAHANDALAM PERTUMBUHAN ORGANISASI - SW, Suprihatmi (Universitas Slamet Riyadi, 2006)
ABTRACT Having a good comprehensive on a change management is necessary in the development of an organization. This change is caused by a dynamical change in the environment both internally and externally such as demography, technology, market, social-politics, strategy, and performance changes. The application of the change management will give a great contribution to the organization in supporting its process to be effective and efficient. There are three processes i.e. the choice process, trajectory process and change process. Key word : Management of Change, The Choices Process, Trajectory Process, Change Process.